Complexes of Mn(II), Co(II), Ni(II), Cu(II) and Zn(II) with ligand formed by condensation reaction of isatin with glutamic acid - Ferenc, Wiesława; Osypiuk, Dariusz; Sarzyński, Jan; Głuchowska, Halina (Eclética Química, 2020)
The complexes of Mn(II), Co(II), Ni(II), Cu(II) and Zn(II) with ligand (H2L=C13H12N2O5) formed by condensation reaction of isatin and glutamic acid were synthesized. Their physico-chemical properties were characterized using elemental analysis, XRF, XRD, FTIR, TG–DSC and TG–FTIR methods and magnetic measurements (Gouy’s and SQUID-VSM methods). The complexes were obtained in crystalline forms (monoclinic or triclinic) with the formulae: M(LH)2·nH2O for Mn(II), Ni(II) and Zn(II) and ML·nH2O for Co(II) and Cu(II), where LH=C13H11N2O5–, L-=C13H10N2O52–, n = 1 for Mn(II), Cu(II) and Zn(II), n = 2 for Co(II) and n = 3 for Ni(II). In air at 293–1173 K they decompose in three steps forming finally the oxides of the appropriate metals. The gaseous decomposition products were identified as: H2O, CO2, CO, hydrocarbons and N2O. The magnetic moment values for complexes (except Zn(II) complex) show their paramagnetic properties with the ferro- and antiferromagnetic interactions between central ions. The compounds of Mn(II) and Co(II) are high spin complexes with weak ligand field. In Co(II) and Cu(II) complexes two carboxylate groups take part in the metal ion coordination while in those of Mn(II), Ni(II) and Zn(II) only one carboxylate anion coordinates to central ion.